Implementasi Manajerial Kepala Sekolah Dalam Meningkatkan Kualitas Kinerja Guru Di SMP Islam Masagi Kabupaten Sukabumi - Herdi Herdi; Mulyawan Safwandy Nugraha (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
An education system without functioning education management or management is unlikely to be able to foster school growth. Management procedures must be implemented systematically and dynamically in the National Education System. The principal as a manager with executive and leadership functions needs to align his internal capabilities in responding to the pressing needs of his environment. Managerial is a process or framework that involves guiding or directing a group of people towards organizational goals or real purposes. For the sake of achieving a successful institution in the realm of education, of course, it is very much determined by the quality of the teacher's performance guided by the Principal. Specifically, this research is intended to explore, analyze and obtain data on planning, organizing, implementing and evaluating the managerial implementation of school principals in improving the quality of teacher performance at Masagi Islamic Middle School, Sukabumi Regency. This study uses a descriptive method with a qualitative approach. Data collection techniques are carried out through observation, interviews and documentation. The research subject is the principal of the school. The results of the research, namely: (1) Planning has been carried out in accordance with applicable guidelines, (2) Organizing is carried out in a balanced manner by prioritizing performance, competence and rank order, (3) Implementation of managerial competencies by seeking effective learning, (4) Evaluation school principals in improving teacher performance by carrying out monitoring and evaluation of each activity that has been carried out, making reports on program implementation and following up on evaluation results. The obstacles faced in efforts to improve teacher performance professionally include the problem of limited human resources in implementing teacher professional capacity building.